Patriarchy And Women’s Agency In Contemporary Indonesian Novels Featuring Madurese Women - Ria Kasanova; Yanti Linarsih; Royyan Julian; Azizah; Windira Nur Azizah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The representation of women in literature is closely related to the construction of gender ideology and power relations in society. In the context of Madurese culture, the values of family honour and social hierarchy play a significant role in shaping gender relations that tend to be patriarchal. This study examines the representation of patriarchal discourse and the negotiation of Madurese women’s agency in contemporary Indonesian novels. This research employs a qualitative approach using Norman Fairclough’s model of critical discourse analysis. The data consist of three contemporary Indonesian novels featuring Madurese female characters: Damar Kambang by Muna Masyari, Paraban Tuah by Elok Teja Suminar, and Silsilah Duka by Dwi Ratih Ramadhany. The findings indicate that patriarchal discourse is constructed through linguistic choices, cultural symbolism, and social narratives that position women as guardians of family honour and objects of social control within family structures, cultural norms, and broader social relations. However, the novels also depict various forms of women’s agency through self-reflection, symbolic resistance to social stigma, and personal decision-making in response to patriarchal pressures. These findings suggest that contemporary Indonesian novels not only reproduce patriarchal discourse but also create discursive spaces for articulating women’s agency within local cultural contexts.